Spatial distribution and determinants of micronutrient intake status among children aged 6–23 months in Ethiopia: A Multi-scale Geographical Weighted Regression Analysis - Alemu Birara Zemariam; Addis Wondmagegn Alamaw; Rediet Woldesenbet Molla; Tesfaye Engdaw Habtie; Molla Azmeraw Bizuayehu; Ribka Nigatu Haile; Tegene Atamenta Kitaw; Biruk Beletew Abate; Mollalign Aligaz Adisu (PLoS ONE, 2025)
Introduction Micronutrient (MN) deficiency is a major global health concern, especially in developing countries like Ethiopia. However, there is a lack of comprehensive monitoring and information regarding MN intake status. This study aimed to assess the spatial distribution and factors influencing the intake of MN-rich foods among children aged 6–23 months in Ethiopia. Methods This study utilized the Ethiopian 2016 Demographic and Health Survey dataset with 2562 weighted children. The Bernoulli model was applied using Kuldorff’s SaTScan version 9.6 software. The spatial distributions of MN-rich food intake were visualized using ArcGIS pro version 3.0 software. Model comparison was conducted using log likelihood ratio and corrected Akakie Information Criteria. A multi-scale geographical weighted regression analysis was performed using MGWR version 2.0 software. A P-value threshold of less than 0.05 was used to identify spatially significant predictors. Results Overall, 69% (95% CI: 60.87, 77.43) of children aged 6–23 months in Ethiopia were found to have consumed foods rich in MN. The intake of these nutrient-rich foods exhibited significant clustering in specific regions, including Addis Ababa, Dire Dawa, Harari, certain parts of Benishangul, and the Gambella region. Spatial scan statistics analysis identified a total of 65 primary spatial clusters. Children residing within the primary clusters were found to be 29% more likely to have an intake of foods rich in MN compared to those living outside the identified clusters (RR = 1.29, LLR = 25.34, P < 0.001). Key spatially significant predictors included higher household wealth status; children aged 13–23 months, the presence of antenatal care, and mothers with any job. Conclusion The consumption of foods rich in MN in Ethiopia displayed non-random spatial patterns. To tackle the problem of inadequate intake of these nutritious foods and address the burden of MN deficiency among children aged 6–23 months, it is essential for policymakers and health planners to implement targeted nutrition interventions in the identified areas and factors.